Analysis of the Causes of Delays in Construction Projects at the XYZ Resort Bali Project - Ikhsan Setiawan; Rooslan Edy Santosa; Fredy Kurniawan; Nyoman Agus Sandika Purnaman (NAROTAMA UNIVERSITY, Indonesia, 2021)
A construction project is a series of interrelated activities to achieve certain objectives (building or construction) within a certain time, cost and quality limitation. Delay in a project is a situation where the project cannot be completed within the planned time. The construction project at the XYZ Resort Bali project, in construction, occurred delays due to disputes. The disputes are caused by several factors between stakeholders, where each stakeholder has various and different problems. The purpose of this study is to identify and analyze the causative factors that contribute to delays in construction projects at the XYZ Resort Bali Project and provide suggestions or determine mitigation measures to overcome them. The method used is a quantitative approach in the form of literature studies, data collection through surveys, data analysis and conclusions. The survey questionnaire was designed based on the factors identified from previous research by determining as many as 6 aspects of the study with 45 types of causes or factors that contributed to project delays. Data analysis was carried out quantitatively descriptive of the delay factor variables from the questionnaire results. The questionnaire data was tested for validity and reliability, then analyzed using the fishbone diagram approach and the House of Risk method to determine the main factors that contribute to project delays and determine mitigation measures to overcome delays in project completion.